2014
DOI: 10.1213/ane.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Orexin-A Levels in Sevoflurane-Remifentanil Anesthesia in Young and Elderly Patients Undergoing Elective Lumbar Surgery

Abstract: Plasma orexin-A levels are not responsible for the delayed emergence from general anesthesia in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Orexin agonists and antagonists have the potential to alter the stability of the anaesthetised state and genetic ablation of orexinergic neurons, which causes acquired murine narcolepsy, delays emergence from anaesthesia without changing anaesthetic induction . In elderly patients this is more confusing, because a delay in awakening could be due to an orexinergic deficit, a decrease in the number of orexin receptors and the tuberomammillary nucleus and activating adrenergic centres’ response to this .…”
Section: Factors That Can Affect the Variability Of Neuronal Inertiamentioning
confidence: 99%
“…Orexin agonists and antagonists have the potential to alter the stability of the anaesthetised state and genetic ablation of orexinergic neurons, which causes acquired murine narcolepsy, delays emergence from anaesthesia without changing anaesthetic induction . In elderly patients this is more confusing, because a delay in awakening could be due to an orexinergic deficit, a decrease in the number of orexin receptors and the tuberomammillary nucleus and activating adrenergic centres’ response to this .…”
Section: Factors That Can Affect the Variability Of Neuronal Inertiamentioning
confidence: 99%
“…As general anaesthesia for surgery in the elderly population is commonly performed, 1 much attention has been given to the ageing-related postoperative cognitive disorders. Many elderly patients undergoing surgical procedures experience delayed emergence from anaesthesia, 2,3 and reduced metabolism and clearance of anaesthetics have been implicated. 3,4 Nevertheless, clinical research has revealed that, even when the ageadjusted minimum alveolar concentration (MAC) is applied, duration of anaesthesia is significantly longer in elderly patients than in middle-aged ones.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…Many elderly patients undergoing surgical procedures experience delayed emergence from anaesthesia, 2,3 and reduced metabolism and clearance of anaesthetics have been implicated. 3,4 Nevertheless, clinical research has revealed that, even when the ageadjusted minimum alveolar concentration (MAC) is applied, duration of anaesthesia is significantly longer in elderly patients than in middle-aged ones. 3 Orexin has a critical role in the sleepewake cycle 5e8 and in anaesthesia arousal regulation, 9e12 and we have found that plasma orexin concentrations in elderly patients are higher compared with adults, 3 consistent with previous observations in a healthy population.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in vivo electrophysiologic recordings of activity are still needed, using c-Fos as a proxy for antecedent activity, neurons within many of these nuclei have been identified to be inhibited during general anesthesia [98,100,101,114]. Moreover, the causal reactivation of some wake-promoting neurons during emergence from the anesthetic state has been explored using approaches such as electrical stimulation, optogenetics, and chemogenetics [115][116][117][118] in rodents and suggested in humans [119]. It is important to note, however, that activation of wake-promoting neurons during emergence does not necessitate that inhibition of the same population occurred during induction of anesthesia, that potential inhibition was causal with respect to the induction of anesthesia, or that experimental reactivation recapitulates spontaneous changes in activity that occur during emergence.…”
Section: Reviewmentioning
confidence: 99%